Diagnosis of the structure and operating processes of the pharmacy and therapeutics committees in two health institutions of the special regime in bogotá (2012)
A structured survey was applied to pharmacy and therapeutics committees of two health entities of the special regime of the Health Social Security System in the city of Bogotá, in order to determine through indicators, the state of organization, process and outcomes. The results were compared to the current regulations since 2005 and international references. Compliance in both cases was relatively low, and limitations were found in its institutional incorporation, as in the absence of comprehensive policies and strategies of formulary system to ensure the selection and control of proper use, as recommended by the World Health Organization and international experience. Further studies are needed on a national representative number of institutions to better identify the effect of the relevant regulations.